Colonization and Succession within the Human Gut Microbiome by Archaea, Bacteria, and Microeukaryotes during the First Year of Life - Wampach, Linda; Heintz-Buschart, Anna; Hogan, Angela; Muller, Emilie E. L.; Narayanasamy, Shaman; Laczny, Cedric C.; Hugerth, Luisa W.; Bindl, Lutz; Bottu, Jean; Andersson, Anders F.; de Beaufort, Carine; Wilmes, Paul (Frontiers in Microbiology, 2017)
Perturbations to the colonization process of the human gastrointestinal tract have been suggested to result in adverse health effects later in life. Although much research has been performed on bacterial colonization and succession, much less is known about the other two domains of life, archaea and eukaryotes. Here we describe the colonization and succession by bacteria, archaea and microeukaryotes during the first year of life (samples collected around days 1, 3, 5, 28, 150 and 365) within the gastrointestinal tract of infants delivered either vaginally or by caesarean section and using a combination of quantitative real-time PCR as well as 16S and 18S rRNA gene sequencing. Sequences from organisms belonging to all three domains of life were detectable in all of the collected meconium samples. The microeukaryotic community composition fluctuated strongly over time and early diversification was delayed in infants receiving formula milk. Caesarean section-delivered (CSD) infants experienced a delay in colonization and succession, which was observed for all three domains of life. Shifts in prokaryotic succession in CSD infants compared to vaginally delivered (VD) infants were apparent as early as on days 3 and 5, which were characterized by increased relative abundances of the genera Streptococcus and Staphylococcus, and a decrease in relative abundance for the genera Bifidobacterium and Bacteroides. Generally, a depletion in Bacteroidetes was detected as early as day 5 postpartum in CSD infants, causing a significantly increased Firmicutes/Bacteroidetes ratio between days 5 and 150 when compared to VD infants. Although the delivery mode appeared to have the strongest influence on differences between the infants, other factors such as a younger gestational age or maternal antibiotics intake likely contributed to the observed patterns as well. Our findings complement previous observations of a delay in colonization and succession of CSD infants, which likely affects not only bacteria but also archaea and microeukaryotes. This further highlights the need for resolving bacterial, archaeal and microeukaryotic dynamics in future longitudinal studies of microbial colonization and succession within the neonatal gastrointestinal tract.